CBIO-01. THERAPEUTIC IMPLICATIONS OF CONDITIONAL VULNERABILITIES CAUSED BY TTFIELDS EXPOSURE IN NOVEL COMBINATION THERAPIES FOR NON-SMALL CELL LUNG CANCER AND BRAIN METASTASES FROM NON-SMALL CELL LUNG CANCER. (9th November 2020) - Kumar Karanam, Narasimha; Story, Michael
Abstract: Tumor Treating Fields (TTFields) are low-intensity, intermediate frequency, alternating electric fields which are FDA-approved for glioblastoma and malignant pleural mesothelioma. Clinical trials are ongoing for other solid tumor cancers, including lung, pancreatic, and ovarian cancers. The initial mechanism for tumor cell killing identified for TTFields exposure was through the disruption of mitosis. Subsequently, it has been shown that TTFields causes replication stress and down-regulates DNA repair and cell cycle checkpoint genes. Here, relative quantitative proteomics were employed to elucidate the cause for the downregulation of DNA repair and cell cycle checkpoint genes. STRING database analysis of differentially expressed proteins revealed interaction networks that included cell cycle, DNA damage repair and replication, and transcriptional and translational regulation. Upstream analysis of key genes associated with cell cycle checkpoint and DNA repair identified reduced expression of the transcriptional activators E2F1 and E2F2 and increased expression of the transcriptional repressor E2F6, suggesting that TTFields affects the CDK–RB–E2F axis. This axis is known to control the transcriptional machinery of the key regulators of cell cycle progression and genome replication fidelity, hence may explain the reduced DNA repair capacity and replication fork maintenance in TTFields-exposed cells. The current study results suggest that TTFields-exposure causes a conditional vulnerability environment that renders cells more susceptible to chemotherapeutic agents that block interfere with the E2F-RB-CDK4/6 axis, inducing DNA damage and replication stress. TTFields-exposure synergistically enhanced the efficacy of the E2F inhibitor HLM006474 with or without the CDK4/6 inhibitor abemaciclib. TTFields plus either or combination of cisplatin and etoposide (known enhancers of replication stress) synergistically enhanced cell killing. These results suggest that the combination of cisplatin and etoposide together with TTFields would be beneficial for non-small cell lung cancer patients and patients with brain metastases from non-small cell lung cancer.